General aspects of quality of life in heterogeneous populations: notes on Flanagan's Quality of Life Scale (QoLS) - Zucoloto,Miriane Lucindo (2019)
Abstract Introduction: Instruments aimed to investigate general aspects of quality of life are scarce in the literature. Flanagan's Quality of Life Scale (QoLS) is an alternative instrument which provides a more comprehensive evaluation of quality of life in different contexts. Objective: To investigate some psychometric properties of the QoLS and discuss the measurement of quality of life using this scale in heterogeneous and large populations. Methods: The QoLS comprises 16 items divided into five dimensions. Responses were measured using a 7-point rating scale. Data were collected from a stratified sample of primary health care users in the municipality of Ribeirão Preto, state of São Paulo, Brazil. Polychoric correlation matrix and exploratory and confirmatory factor analyses were performed. Results: A total of 1,054 primary health care users in 12 health care facilities were interviewed: 79.7% female; mean age = 36.97 years (standard deviation = 15.1). Moderate to low correlation coefficients were observed between almost all pairs of QoLS items. Items 7 and 9 as well as items 14 and 15 were the pairs presenting the highest correlation coefficient. The original structure of the QoLS, with five dimensions, showed adequate psychometric properties regarding the data collected. The inclusion of a single item on life satisfaction was proposed. Conclusion: The original structure of the QoLS was validated and found to be reliable when applied to primary health care users. A new general item was suggested for future studies to improve the interpretations and associations regarding general aspects of quality of life in large and heterogeneous populations.